Emotional faces in neutral crowds: Detecting displays of anger, happiness, and sadness on schematic and photographic images of faces - Lipp, Ottmar; Price, S.; Tellegen, C. (Springer Netherlands, 2009)
Detection of angry, happy and sad faces among neutral backgrounds was investigated in three single emotion tasks and an emotion comparison task using schematic (Experiment 1) and photographic faces (Experiment 2). Both experiments provided evidence for the preferential detection of anger displays over displays of other negative or positive emotions in tasks that employed all three target emotions. Evidence for preferential detection of negative emotion in general was found only with schematic faces. The present results are consistent with the notion that the detection of displays of anger, and to some extent sadness, does not reflect on a pre-attentive mechanism, but is the result of a more efficient visual search than is the detection of positive emotion. © 2009 Springer Science+Business Media, LLC.